A comparison of Australians, Chinese and Sri Lankans' payment preference at point-of-sale. Issue 1 (25th August 2021) - Senali, Madugoda Gunaratnege; Cripps, Helen; Meek, Stephanie; Ryan, Maria M.
Abstract : Purpose: The rise of digital transaction technology has been transformative for businesses however consumer attitudes to this technology can vary. The comparison of Australians, Chinese and Sri Lankans' consumers salient attitudes toward payment methods at the Point-of-Sale (POS) provides businesses with insights into the factors impacting consumers' payment preference. Design/methodology/approach: A qualitative methodology was employed for data collection from Australian, Chinese and Sri Lankan participants. A combination of focus groups and individual interviews were carried out with a total of 35 participants. Findings: Results indicate that factors of perceived relative advantage, perceived compatibility, perceived risk, perceived rewards, perceived situations and social influence impact consumers' payment preference at POS across all three countries, however the degree of impact varies in importance across the three countries. Practical implications: In the cross-cultural comparison of the consumers' payment preference, this research highlights the complex interplay of factors that shapes these payment preferences. The findings, given the growing digitization of transactions, provides banking and financial institutions with a foundational model that can be used to improve their services and business model. Originality/value: Previous studies failed to distinguish between payment choice at the time of the transaction and payment preference which is repeated behaviour. This study is the first to compare the consumers' payment preference across Australian, Chinese and Sri Lankan consumers and responds to calls for additional research that generalises consumers' payment preferences across cultures.